2008
DOI: 10.1111/j.1467-7687.2008.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

To see or not to see: infants prefer to follow the gaze of a reliable looker

Abstract: In two experiments, we examined whether 14-month-olds understand the subjective nature of gaze. In the first experiment, infants first observed an experimenter express happiness as she looked inside a container that either contained a toy (reliable looker condition) or was empty (unreliable looker condition). Then, infants had to follow the same experimenter's gaze to a target object located either behind or in front of a barrier. Infants in the reliable looker condition followed the experimenter's gaze behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
108
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 65 publications
(85 reference statements)
8
108
5
Order By: Relevance
“…For example, in an unreliable-labeler task, 16-month-olds looked longer at an agent who provided incorrect labels for familiar objects if she faced the objects than if she faced away from them (Koenig & Echols, 2003; for related work with preschoolers, see Koenig, Clement, & Harris, 2004;Koenig & Harris, 2005). Building on these results, Poulin-Dubois and her colleagues tested 14-to 16-month-olds in a series of unreliable-looker tasks: These examined whether infants, after watching an agent act in a manner either consistent or inconsistent with her epistemic states in a first context, would hold expectations about her behavior in a second context (Chow et al, 2008;Chow & Poulin-Dubois, 2009;Poulin-Dubois et al, 2011). In the first context, the agent expressed excitement ("Wow!")…”
Section: Epistemic States and The Consistency Principlementioning
confidence: 99%
See 4 more Smart Citations
“…For example, in an unreliable-labeler task, 16-month-olds looked longer at an agent who provided incorrect labels for familiar objects if she faced the objects than if she faced away from them (Koenig & Echols, 2003; for related work with preschoolers, see Koenig, Clement, & Harris, 2004;Koenig & Harris, 2005). Building on these results, Poulin-Dubois and her colleagues tested 14-to 16-month-olds in a series of unreliable-looker tasks: These examined whether infants, after watching an agent act in a manner either consistent or inconsistent with her epistemic states in a first context, would hold expectations about her behavior in a second context (Chow et al, 2008;Chow & Poulin-Dubois, 2009;Poulin-Dubois et al, 2011). In the first context, the agent expressed excitement ("Wow!")…”
Section: Epistemic States and The Consistency Principlementioning
confidence: 99%
“…Finally, additional experiments indicated that older infants realize that, just as they may see an object that an agent cannot see, an agent may see an object that they themselves cannot 46 see (e.g., Chow, Poulin-Dubois, & Lewis, 2008;Moll & Tomasello, 2004;Repacholi, 1998 Together, these results suggested that infants 12 months and older are capable of simple perspective-taking: They realize that an agent's representation of a scene may differ from their own, and in such cases they use the agent's perspective to interpret and respond to her actions.…”
Section: Perspective-taking In Older Infantsmentioning
confidence: 99%
See 3 more Smart Citations